Application of Five-Finger Hypnosis to Reduce Pain in Postoperative Patients with Appendectomy - Pratama, Siska Vaniya; Punjastuti, Budi (Global Health Science Group, 2024)
Appendectomy is a treatment through a surgical procedure to remove or remove an infected appendix. The act of an appendectomy causes pain. Pain is caused by chemical mediator stimulation due to mechanical stimulation of the wound. Non-pharmacological measures taken to reduce pain, namely five-finger hypnosis is a form of self-hypnosis that can provide a high relaxation effect. According to medical record data from Sleman Hospital in 2023, the number of patients undergoing appendectomy surgery is 202 cases. Objective: To describe how the application of five-finger hypnosis to reduce pain in post-operative appendectomy patients. Method: Using a descriptive method where this method obtains a systematic and accurate description of real events with a nursing application approach. Results: After five-finger hypnosis therapy for 3 consecutive days with a frequency of 2 times a day within 15 minutes, the pain scale of 6 (moderate pain) decreased to 1 (mild pain). Conclusion: Five-finger hypnosis therapy is effective in reducing pain in postoperative patients with appendectomy from moderate to mild scale.